Performance Vs. Potential – What’s More Important? - Khatri, Reeta; Rana, Geeta (International Journal of Psychosocial Rehabilitation, 2020)
-The paper describe how an electric middle size enterprise in India improved their employee’s performance while eliminating forced rankings and ratings. The paper reveals how employees involve in a strength based self-goal and regular feedback system. Rewards and recognition is an excellent platform to identify and nurture the talent in company and used as a mechanism to groom employees. This strategy also promote effective behaviour, and has the potential to create a bigger change in the form of work culture. The paper outlines that process of developing potential of employees which add value to the business and recalibrated the expectations of the new age workers.